Iulius–Claudiuslar Dönemi’nde Likya ve Pamfilya’da imparator kültü - Yener, Enise (My University, 2022)
“İmparator kültü” kavramı kişinin öldükten sonra veya henüz hayattayken tanrılaştırılarak kültünün kurulması anlamına gelir. Kişinin tanrılaştırılmasının ilk örnekleri M.ö. III. binyılda Eski Doğu medeniyetlerinde görülür. Kişinin tanrılaştırılması Helen kültüründeki “kahraman kültü” ve “kurucu kültü” geleneği sayesinde gelişerek III. Aleksandros zamanında “hükümdar kültüne” dönüşür. Roma’nın Küçük Asya’ya yayılmasıyla birlikte Romalılar için kurulan kültler, imparatorluk rejimine geçilmesiyle imparator için kurulmaya başlar ve günümüzde Teke yarımadası ile sınırlanan Lykia ve Antalya ilini içine alan Pamphylia bölgelerinde Iulius–Claudiuslar hanedanına mensup imparatorlar için pek çok kült kurulur. Bu çalışmamızda Lykia ve Pamphylia tarihiyle ilgili genel bir değerlendirme yapıldıktan sonra Caesar’dan başlayarak Iulius–Claudiuslar hanedanına mensup imparatorların “imparator kültüne” dair düşüncelerine ve O’nlar için kurulan kültlere temas edilmiştir.

The term “emperor cult” refers to the establishment of a cult through the deification of a person after death or while still alive. The first examples of the deification of a person are found in the Ancient Eastern civilizations in the third millennium BC. The deification of the person develops thanks to the tradition of the “hero cult” and the “founder cult” in the Hellenic culture and turns into a “ruler cult” in the III. Alexandros period. With the expansion of Rome in Asia Minor, the cults established for the Romans began to be established for the emperor with the transition to the imperial regime, and many cults were established for the emperors belonging to the Julio–Claudian dynasty in the regions of Lycia and Pamphylia, which today border by the Teke Peninsula and include the province of Antalya. In this study, after a general evaluation of the history of Lycia and Pamphylia, the views of the emperors of the Julio–Claudian dynasty on the “emperor cult” and the cults established for them are discussed.
Keywords: History, Ancient; Iulius–Claudiuslar; İmparator Kültü; Julio–Claudian; Lykia; Pamphylia; Pamphylia Emperor Cult; Tarih, Eski Çağ